2022
DOI: 10.1186/s12905-022-01630-3
|View full text |Cite
|
Sign up to set email alerts
|

“I felt like she didn’t take me seriously”: a multi-methods study examining patient satisfaction and experiences with polycystic ovary syndrome (PCOS) in Canada

Abstract: Background Polycystic ovary syndrome (PCOS) is a common and complex condition affecting metabolic, reproductive, cardiovascular, and psychological health in women. Previous studies point to widespread dissatisfaction and delays with the diagnosis of PCOS and a lack of information provision by doctors, with few studies on Canadian populations. This multi-methods study explored the perceptions and experiences of PCOS diagnosis in Canada using an online-distributed survey and follow-up, in-depth, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 60 publications
2
17
1
Order By: Relevance
“…While previous research in Caucasian women has reported dissatisfaction with delayed diagnosis and inadequate information [20,34,35], we report here novel findings from this large, international study of ethnic Indian women with PCOS relating to reluctance in healthcare seeking and the use of inappropriate educational resources. Although the majority of participants were young, university educated and working for wages, yet they reported delays in seeking treatment after the onset of symptoms.…”
Section: Discussioncontrasting
confidence: 41%
“…While previous research in Caucasian women has reported dissatisfaction with delayed diagnosis and inadequate information [20,34,35], we report here novel findings from this large, international study of ethnic Indian women with PCOS relating to reluctance in healthcare seeking and the use of inappropriate educational resources. Although the majority of participants were young, university educated and working for wages, yet they reported delays in seeking treatment after the onset of symptoms.…”
Section: Discussioncontrasting
confidence: 41%
“…In-depth, semistructured telephone interviews with participants explored their experiences in being diagnosed and subsequently managing PCOS. As described in a prior paper, 28 interview participants were sourced from a larger, multi-methods study that involved an online questionnaire about PCOS diagnosis experience hosted on SurveyMonkey (Momentive Inc., San Mateo, California, USA). Respondents who indicated interest in being interviewed at the end of their questionnaires were subsequently interviewed remotely, via telephone, on a first-come, first-served basis.…”
Section: Methodsmentioning
confidence: 99%
“…This is often conveyed in the discussion section of a publication. Ismayilova and Yaya (2022) conducted a mixed methods study with the aim to better understand the experiences and satisfaction of education provided to women being diagnosed with polycystic ovarian syndrome (PCOS). In ).…”
Section: Exploratory Sequentialmentioning
confidence: 99%